Free-standing composite hydrogel films for superior volumetric capacitance1. Issue 30 (14th August 2015) - Moussa, Mahmoud; Zhao, Zhiheng; El-Kady, Maher F.; Liu, Huakun; Michelmore, Andrew; Kawashima, Nobuyuki; Majewski, Peter; Ma, Jun
<x xml:space="preserve">Abstract</x> Flexible, free-standing, high-performance supercapacitor electrodes were created by the development of a conducting composite hydrogel where graphene oxide sheets were in situ reduced by polyaniline.